The boy in the striped pajamas : a fable - Boyne, John, 1971- (Vintage, 2006)
Bored and lonely after his family moves from Berlin to a place called "Out-With" in 1942, Bruno, the son of a Nazi officer, befriends a boy in striped pajamas who lives behind a wire fence.